Identification of Beche-de-mers from Indonesia by molecular approach - GINTUNG PATANTIS; ARIYANTI S DEWI; YUSRO N FAWZYA; MUHAMMAD NURSID (Society for Indonesian Biodiversity, 2019)
Abstract. Patantis G, Dewi AS, Fawzya YN, Nursid M. 2019. Identification of Beche-de-mers from Indonesia by molecular approach. Biodiversitas 20: 537-543. Sea cucumbers have been commercially traded around the world due to their nutritional values and health benefits. Sea cucumbers are marketed as processed sea cucumber, also known as beche de mer, teripang, haisen or gamat. Due to the high global demand of beche-de-mers, there have been several cases of fraud due to the visual shape and color similarities of processed sea cucumbers. Additionally, the local name diversity of Indonesian sea cucumbers making the identification of beche-de-mers difficult. Therefore, this study aimed to identify commercial sea cucumbers from selected locations in Indonesia by molecular approach. The targeted Cytochrome c oxidase subunit I (COI) was used in this research. A total of 25 beche-de-mers was purchased from local markets in Indonesia, i.e. Boalemo (17 local names), Pesawaran (5), Surabaya (2) and West Lombok (1). Results showed that 22 species of beche-de-mer were successfully identified, ie. Acaudina sp., Actinopyga echinites, A. lecanora, A. miliaris, Bohadschia argus, B. marmorata, B. ocellata, B. vitiensis, Holothuria sp. H. atra, H. coluber, H. edulis, H. excellens, H. fuscocinerea, H. fuscogilva, H. fuscopunctata, H. scabra, Pearsonothuria graeffei, Phyrella sp., Stichopus herrmanni, S. horrens and S. monotuberculatus. The identification of Indonesian beche-de-mers using molecular method could support the identification of the local sea cucumbers to overcome mislabeled and fraud. Correct identification is important for the record of beche-de-mer trade in Indonesia and further conservation management.